Depression and symptomatic response among HIV-infected drug users enrolled in a randomized controlled trial of directly administered antiretroviral therapy. - Springer, Sandra A; Chen, Shu; Altice, Frederick (AIDS care, 2009)
Depression is highly prevalent among HIV-infected injection drug users (IDUs) and has been associated with poor adherence to antiretroviral therapy and increased morbidity and mortality. Factors associated with changes in depressive symptoms among this group receiving antiretroviral treatment that have not been extensively evaluated.
Keywords: Adult; Anti-HIV Agents; Depressive Disorder; Directly Observed Therapy; Epidemiologic Methods; Female; HIV Infections; HIV-1; Humans; Male; Patient Acceptance of Health Care; Substance Abuse, Intravenous